Do Vaccines Need a Gender Perspective? Influenza Says Yes! - Sánchez-de Prada, Laura; Ortiz de Lejarazu-Leonardo, Raúl; Castrodeza-Sanz, Javier; Tamayo-Gómez, Eduardo; Eiros-Bouza, José María; Sanz-Muñoz, Iván (Frontiers in Immunology, 2021)
Background Sex differences in immune responses are well known. However, the humoral response in males and females in the case of influenza vaccination is yet to be characterized since studies have shown uneven results. Methods A retrospective study was conducted in 2,243 individuals (46.9% males) divided by age (15–64 and ≥65 years old). A serological analysis was performed by hemagglutination inhibition assay (HI) just before and 28 days after annual vaccination against seasonal influenza viruses in people vaccinated during the 2006–2018 seasons. A comparison of the humoral responses against influenza A and B viruses contained in the vaccine, between male and female individuals in young adults and elderly was conducted. Results Significative higher humoral response against classical influenza A (H1N1), A(H1N1)pdm09 subtype and B/Victoria lineage in terms of seroconversion rate were found in elderly women. No significant differences were found in the case of A(H3N2) subtype. Conclusions Elderly women seem to display a greater humoral response against classical A(H1N1), pandemic A(H1N1)pmd09 and B/Victoria lineage than elderly men. Sex dimorphism does not affect young adults.